EVALUASI TINGKAT PENERIMAAN DAN PENGGUNAAN APLIKASI JAKI DENGAN MENGGUNAKAN MODEL UNIFIED THEORY ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) (STUDI KASUS: FAKULTAS ILMU KOMPUTER UPN "VETERAN" JAKARTA) - Erina Yuniar (2021)
In order to provide better public service facilities by utilizing information technology, the Jakarta Smart City Management Unit released the JAKI (Jakarta Kini) application. During a pandemic like this time, the JAKI application is very useful to find out the latest information about the development of the Covid-19 pandemic in DKI Jakarta. This research is intended to provide insight into the factors that influence the use of the JAKI application. The modeling used in the research is Unified Theory Acceptance and Use of Technology (UTAUT) modeling which focuses on the variables of performance expectancy, facilitating conditions, effort expectancy, social influence, use behavior, and behavior intention. The benefits of this study are to provide insight into how much the variables in the UTAUT model affect the acceptance and use of the JAKI application and provide recommendations which are expected to be taken into consideration by the JAKI application manager to increase acceptance and use of the JAKI application. Sampling was carried out by purposive sampling technique with the population used as the sample were students of the Faculty of Computer Science UPN "Veteran" Jakarta who were users of the JAKI application. Based on the analysis carried out using PLS-SEM, it is known that the JAKI application is accepted by students of the Faculty of Computer Science and that usage behavior is influenced by aspects of behavior intention by 82.5%. The intention to use the JAKI application is influenced by the performance expectancy aspect of 21.5%, the effort expectancy of use is 30%, and the social influence is 21.1%. While the aspect of facilitating conditions has a positive but insignificant effect and only has an effect of 4.3% on the behavior of using the JAKI application.